(untitled) (International Journal of Islamic Business, 2016)
This study explores the contingency theory to explain the risk management practices in Islamic and conventional banks in Kazakhstan, an emerging Islamic banking hub of the Central Asia. The outcome of this study helps identify the contingency variables that explain the risk management challenges faced by Islamic bankers in Kazakhstan with respect to other Islamic markets, such as Indonesia and Malaysia. In order to explore the contingency variables influencing the risk management process and performance, this study utilised multiple layers and sources of information. Firstly, using semi-structured protocols, we interviewed top, middle and operation-level risk managers from large and small Islamic and conventional banks of Kazakhstan. We extended the surveys to Indonesia and Malaysia to learn from already established risk management system. Secondly, we find that several risk related financial ratios to strengthen our findings. Risk management system is influenced by the type of risks and a number of contingency variables. Credit, operational and market risks are the three major risks for Islamic banks in Kazakhstan. Limited know-how of risk management and limited use of technology are the two most important firm specific contingency variables. Limited secondary market, limited regulatory assistance, and limited use of derivatives are the three most important industry specific contingency variables that have great influence on the risk management of Islamic banks. The influence of industry-specific factors is apparently bolder than the influence of firm-specification limitations. We also find that the size of the market influences all the stages of enterprise risk management, which has been identified as a contingent variable by previous studies on non-financial sector. The results are vitally important for Kazakhstan as the country is planning to turn the economy into a hub of Islamic finance in the Central Asia. Management of Islamic banks that are planning to invest in Kazakhstan can learn from the challenges and gaps explained in this study. The Central Bank of Kazakhstan may take an active role in establishing prudential regulations to ensure investment in human capital, technology- and customer-centric banking operation, and innovation to tackle risk management challenges. This study is one of the preliminary studies that discusses about risk management of Islamic bank in Kazakhstan, and compares the risk management practices and performance with established banks from other countries. We have redrawn the contingency framework for risk management in Islamic banks.